Composition, electroconductive film, capacitor, and battery

JP2023172604A5Pending Publication Date: 2025-03-26IDEMITSU KOSAN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022084527
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-05-24
Publication Date
2025-03-26

AI Technical Summary

Technical Problem

Conductive polymers, such as polyaniline, are difficult to mold due to their insolubility and infusibility, and adjusting viscosity through concentration or adding binders compromises conductivity or durability.

Method used

A composition comprising conductive polymer, phenolic compound, thickener, and solvent, with specific ratios and additives to control viscosity and maintain conductivity, using a polyaniline composite doped with a proton donor.

Benefits of technology

Achieves a wide range of viscosity control while maintaining practical conductivity levels, suitable for various coating methods, and forms durable conductive films with high electrical conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000026_0000
    Figure 00000026_0000
  • Figure 00000026_0001
    Figure 00000026_0001
  • Figure 00000026_0002
    Figure 00000026_0002
Patent Text Reader

Abstract

To provide a composition that can achieve viscosity improvement surpassing the outcomes obtained from simple adding of thickeners, and also provide a conductive film, a capacitor and a battery.SOLUTION: A composition contains (a) an electroconductive polymer, (b) a phenol compound, (c) a thickener, and (d) a solvent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to compositions, conductive films, capacitors, and batteries. [Background technology]

[0002] Conductive polymers are used as solid electrolytes in capacitors, electromagnetic wave absorbing coatings, antistatic coatings, electrolytic plating undercoats, conductive inks for circuit wiring, and other applications. Polyaniline, a type of conductive polymer, has advantages and properties such as its electrical properties, the fact that it can be synthesized relatively easily from inexpensive aniline, and its excellent stability against oxygen and other elements while exhibiting conductivity.

[0003] Polyaniline with high conductivity can be easily obtained by the method described in Patent Document 1. Conductive polymers are generally insoluble and infusible, making them difficult to mold. In recent years, water-dispersible or organic solvent-soluble conductive polymers have been developed, making them easier to mold and process. This allows for the formation of conductive polymer films through coating and printing, imparting various functionalities. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] International Patent Publication No. 2012 / 102017 [Overview of the project] [Problems that the invention aims to solve]

[0005] The object of the present invention is to provide a composition, a conductive film, a capacitor, and a battery that can achieve excellent viscosity improvement beyond the effect of simply adding a thickening agent. [Means for solving the problem]

[0006] It has a viscosity suitable for coating and printing methods. Usually, in order to adjust the viscosity, it is necessary to change the concentration of the conductive polymer or the solvent composition. In this case, when the concentration of the conductive polymer is increased, the viscosity increases, but the cost as a material becomes high and it is not practical. When the concentration is decreased, the viscosity decreases, but a very thin coating film is formed, the durability is low, and a high-resistance film is formed, which is also not practical. Also, in some cases, a large amount of binder may be blended to increase the viscosity, but in this case, the conductivity of the obtained coating film is significantly reduced. The inventors have found a composition that can obtain a conductive film with a viscosity controlled over a wide range and maintaining conductivity within a practical range, and have reached the invention.

[0007] According to the present invention, the following compositions and the like are provided. 1. (a) A conductive polymer, (b) A phenolic compound, (c) A thickener, and (d) A solvent, a composition containing the same. 2. The composition according to 1, wherein the component (a) is a polyaniline complex obtained by doping a proton donor into substituted or unsubstituted polyaniline. 3. The composition according to 2, wherein the proton donor is a proton donor represented by the following formula (I). M(XARn)m (I) (In the formula (I), M is a hydrogen atom, an organic free radical or an inorganic free radical. X is an acidic group. A is a hydrocarbon group which may contain a substituent. R is, independently of each other, -R 1 , -OR 1 , -COR 1 , -COOR 1 , -CO(COR 1 )、又は―CO(COOR 1 ) is a substituent represented by. R 1 is a hydrocarbon group having 4 or more carbon atoms which may contain a substituent, a silyl group, an alkylsilyl group, -(R 2 O) x -R 3 a group represented by, or -(OSiR3 2) x -OR 3 (R 2 is an alkylene group, R 3 The groups are represented by (where x is an integer greater than or equal to 1), where each group may be the same or different hydrocarbon group. n is an integer greater than or equal to 2. m is the valence of M. 4. The composition according to any one of 1 to 3, wherein the content of component (c) is 0.1% by mass or more based on 100% by mass of the entire composition. 5. The composition according to any one of claims 1 to 4, wherein the mass ratio of the content of component (a) to the content of component (c) is 1:0.01 to 1:2. 6. The composition according to any one of 1 to 5, wherein component (c) is a polyether compound or a cellulosic compound. 7. A composition according to any one of 1 to 6, wherein the viscosity is 2 to 1000 mPa·s. A conductive film comprising any of the compositions described in 8.1 to 8.7. A capacitor containing the conductive film described in 9.8. A battery containing the conductive film described in 10.8. [Effects of the Invention]

[0008] According to the present invention, it is possible to provide compositions, conductive films, capacitors, and batteries that can achieve excellent viscosity improvements that go beyond the effects of simply adding a thickening agent. [Brief explanation of the drawing]

[0009] [Figure 1] This figure shows the upper surface of the glass substrate on which the indium tin oxide (ITO) electrode is formed, as used in Example 1. [Figure 2] This figure shows the upper surface of the glass substrate prepared in Example 1, in which the conductive film was removed to expose the terminals of the ITO electrode on the surface. [Figure 3] This diagram shows the synergistic effect of component (b) and component (c). [Modes for carrying out the invention]

[0010] [Composition] A composition according to one aspect of the present invention is (a) Conductive polymer (hereinafter also referred to as "component (a)") (b) Phenolic compounds (hereinafter also referred to as "component (b)") (c) Thickening agents (hereinafter also referred to as "component (c)"), and (d) A solvent (hereinafter also referred to as "component (d)") is included.

[0011] This allows for a superior improvement in viscosity that goes beyond the effect of simply adding a thickening agent. Furthermore, as an optional effect, it is possible to achieve both the conductivity of the resulting conductive film (e.g., 0.5 S / cm or higher) and the viscosity of the composition.

[0012] The viscosity of a composition according to one aspect of the present invention is, from the viewpoint of coating properties, for example, 1 to 500 mPa·s, 2 to 500 mPa·s, 3 to 400 mPa·s, 5 to 300 mPa·s, 1 to 1000 mPa·s, 2 to 1000 mPa·s, 3 to 700 mPa·s, 10 to 500 mPa·s, or 16 to 200 mPa·s. The viscosity of the composition is measured using a tuning fork type vibrating viscometer SV-1H (manufactured by A&D Company, Limited).

[0013] The following describes each component.

[0014] (Component (a): conductive polymer) Examples of conductive polymers include polyaniline, polythiophene, polypyrrole, and their derivatives. These polymers may or may not have substituents. They may be used individually or in combination of two or more.

[0015] Polyaniline is preferred as the conductive polymer. The polyaniline preferably has a weight-average molecular weight of 10,000 or more, more preferably 20,000 or more, even more preferably 30,000 to 1,000,000, even more preferably 40,000 to 1,000,000, and particularly preferably 52,000 to 1,000,000.

[0016] The weight-average molecular weight of polyaniline is measured by the method described in the examples.

[0017] Polyaniline may or may not have substituents, but from the viewpoint of versatility and economics, unsubstituted polyaniline is preferred. Examples of substituents include linear or branched hydrocarbon groups such as methyl, ethyl, hexyl, and octyl groups; alkoxy groups such as methoxy and ethoxy groups; aryloxy groups such as phenoxy groups; and halogenated hydrocarbons such as trifluoromethyl (-CF3) groups.

[0018] Furthermore, from the viewpoint of conductivity, it is preferable that the polyaniline complex is a polyaniline doped with a proton donor, either substituted or unsubstituted. The doping of polyaniline with a proton donor can be confirmed by ultraviolet-visible-near-infrared spectroscopy or X-ray photoelectron spectroscopy, and the proton donor can be used without any particular chemical structural limitations as long as it has sufficient acidity to generate carriers in the polyaniline. Using this polyaniline composite is preferable because it improves solubility in solvents.

[0019] Examples of proton donors include Brønsted acids or salts thereof, preferably organic acids or salts thereof (e.g., sulfonic acids or sulfonates), and more preferably, from the viewpoint of solubility, proton donors represented by the following formula (I). M(XAR n ) m (I) (In formula (I), M is a hydrogen atom, an organic free radical, or an inorganic free radical.) X is an acidic group. A is a hydrocarbon group that may contain substituents. R is independent of each other, -R 1 , -OR 1 , -COR 1 ,-COOR 1 , -CO(COR 1 ), or -CO(COOR 1 There is a substituent represented by ). R 1 This may contain substituents on hydrocarbon groups having 4 or more carbon atoms, silyl groups, alkylsilyl groups, -(R 2 O) x -R 3 A base represented by -(OSiR 3 2) x -OR 3 (R 2 is an alkylene group, R 3 The groups are represented by (where x is an integer greater than or equal to 1), where each group may be the same or different hydrocarbon group. n is an integer greater than or equal to 2. m is the valence of M.

[0020] In the above formula (I), M is a hydrogen atom, an organic free radical, or an inorganic free radical. Examples of the above-mentioned organic free radicals include pyridinium groups, imidazolium groups, and anilinium groups. Examples of the above-mentioned inorganic free radicals include sodium, lithium, potassium, cesium, and ammonium.

[0021] X is an acidic group, for example, -SO3 - , -PO3 2- -PO4(OH) - ,-OPO3 2- -OPO2(OH) - , -COO - Examples of groups represented by -SO3 include - A base represented by is preferred.

[0022] A is a hydrocarbon group that may contain substituents. Examples of hydrocarbon groups include linear or branched alkyl groups having 1 to 24 carbon atoms (preferably 1 to 8, more preferably 1 to 4 carbon atoms) (e.g., ethylene group); alkenyl groups; cycloalkyl groups which may contain substituents such as cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, and menthyl; dicycloalkyl or polycycloalkyl groups which may be condensed, such as bicyclohexyl, norbornyl, and adamantyl; aryl groups containing aromatic rings which may contain substituents such as phenyl, tosyl, thiophenyl, pyrrolinyl, pyridinyl, and furanyl; diaryl or polyaryl groups which may be condensed, such as naphthyl, anthracenyl, fluorenyl, 1,2,3,4-tetrahydronaphthyl, indanyl, quinolinyl, and indonyl; alkylaryl groups, etc., with the corresponding (n+1) valency group.

[0023] R is independent of each other, -R 1 , -OR 1 , -COR 1 ,-COOR 1 , -CO(COR 1 ), or -CO(COOR 1 There is a substituent represented by ). R 1 This may include substituents (e.g., alkyl groups having 1 to 4 carbon atoms (preferably methyl, ethyl, or propyl groups)) of hydrocarbon groups having 4 or more carbon atoms (e.g., 4 to 8 or 4 to 12 carbon atoms), silyl groups, alkylsilyl groups, -(R 2 O) x -R 3 A base represented by -(OSiR 3 2) x -OR 3 (R 2 is an alkylene group, R 3 The groups are represented by (where x is an integer greater than or equal to 1), where each group may be the same or different hydrocarbon group. R 1 Examples of hydrocarbon groups include straight-chain or branched butyl groups, pentyl groups, hexyl groups, heptyl groups, octyl groups, nonyl groups, decyl groups, dodecyl groups, pentadecyl groups, eicosanyl groups, and the like. n is an integer greater than or equal to 2 (for example, 2 to 4, or 2 to 3). m is the valence of M.

[0024] The proton donor represented by formula (I) is preferably a dialkylbenzenesulfonic acid, a dialkylnaphthalenesulfonic acid, a sulfophthalic acid ester, or a proton donor represented by the following formula (II) (an organic protonic acid or a salt thereof). M(XCR 4 (CR 5 2COOR 6 )COOR 7 ) p (II)

[0025] In equation (II) above, M and X are the same as in equation (I). p is the valence of M.

[0026] R 4 and R 5 Each is independently a hydrogen atom, a hydrocarbon group, or R 8 A group represented by 3Si- (where R 8 It is a hydrocarbon group, and has three R 8 (They may be the same or different.) R 4 and R 5 Examples of hydrocarbon groups include linear or branched alkyl groups having 1 to 24 carbon atoms; aryl groups containing aromatic rings; and alkylaryl groups. R 8 The hydrocarbon group is R 4 and R 5 It is similar to the hydrocarbon group.

[0027] R 6 and R 7 Each is independently a hydrocarbon group or -(R 9 O) q -R 10 A base represented by [where R 9 R is a hydrocarbon group or a silylene group, 10 is a hydrogen atom, hydrocarbon group or R 11 The group represented by 3Si- (R 11is a hydrocarbon group, and three Rs 11 may be the same or different), and q is an integer of 1 or more]. R 6 and R 7 Examples of the hydrocarbon group of include linear or branched alkyl groups having 1 to 24 carbon atoms, preferably 4 or more carbon atoms (for example, 4 to 10, or 4 to 14); aryl groups containing an aromatic ring; alkylaryl groups, and the like. R 6 and R 7 Specific examples of the hydrocarbon group of include linear or branched butyl groups, pentyl groups, hexyl groups, octyl groups (for example, 2-ethylhexyl), decyl groups, and the like.

[0028] R 9 Examples of the hydrocarbon group of include linear or branched alkylene groups having 1 to 24 carbon atoms; arylene groups containing an aromatic ring; alkylarylene groups; arylalkylene groups, and the like. Also, the hydrocarbon group of R 10 and R 11 is the same as in the case of R 4 and R 5 . It is preferable that q is an integer of 1 to 10.

[0029] R 6 and R 7 are groups represented by -(R 9 O) q -R 10 Specific examples of the acid of the proton donor represented by formula (II) in the case of being a group represented by include acids represented by the following formula.

Chemical formula

[0030] The proton donor (organic protonic acid or its salt) represented by the above formula (II) is preferably a sulfosuccinic acid derivative represented by the following formula (III). M(O3SCH(CH2COOR 12 )COOR 13 1]) m(III) In equation (III) above, M and m are the same as in equation (I) above.

[0031] R 12 and R 13 Each is independently a hydrocarbon group or -(R 14 O) r -R 15 A base represented by [where R 14 R is a hydrocarbon group or a silylene group, 15 is a hydrogen atom, hydrocarbon group or R 16 A group represented by 3Si- (where R 16 It is a hydrocarbon group, and has three R 16 (These may be the same or different), and r is an integer greater than or equal to 1.

[0032] R 12 and R 13 The hydrocarbon group is R 6 and R 7 It is similar to the hydrocarbon group. R 14 The hydrocarbon group is R 9 It is similar to the hydrocarbon group of R. 15 and R 16 The hydrocarbon group is R 4 and R 5 It is similar to the hydrocarbon group. r is preferably an integer between 1 and 10.

[0033] R 12 and R 13 However, -(R 14 O) r -R 15 A specific example of a sulfosuccinic acid derivative represented by formula (III) when the group is represented by R is: 6 and R 7 ga-(R 9 O) n -R 10 This is similar to the proton donor represented by formula (II) when it is a group represented by . R 12 and R 13 The hydrocarbon group is R 6 and R7 Similar to hydrocarbon groups, butyl groups, hexyl groups, 2-ethylhexyl groups, decyl groups, etc., are preferred.

[0034] The doping rate of the proton donor to polyaniline is preferably 0.30 to 0.65, more preferably 0.32 to 0.60, even more preferably 0.33 to 0.57, and particularly preferably 0.34 to 0.55. If the doping rate is 0.30 or higher, the solubility of the polyaniline complex in organic solvents is sufficiently high. The doping rate is defined as (moles of proton donors doping the polyaniline) / (moles of monomer units of polyaniline). For example, a doping rate of 0.5 for a polyaniline complex containing unsubstituted polyaniline and a proton donor means that there is one proton donor doped for every two monomer units of polyaniline. The doping rate can be calculated if the number of moles of proton donors and polyaniline monomer units in the polyaniline complex can be measured. For example, if the proton donor is an organic sulfonic acid, the number of moles of sulfur atoms derived from the proton donor and the number of moles of nitrogen atoms derived from the polyaniline monomer units can be quantified using organic elemental analysis, and the doping rate can be calculated by taking the ratio of these values.

[0035] The polyaniline complex preferably comprises unsubstituted polyaniline and a sulfonic acid as a proton donor, and satisfies the following formula (5). 0.32 ≤ S5 / N5 ≤ 0.60 (5) (In the formula, S5 represents the total number of moles of sulfur atoms contained in the polyaniline complex, and N5 represents the total number of moles of nitrogen atoms contained in the polyaniline complex. The above moles of nitrogen atoms and sulfur atoms were measured by organic elemental analysis.)

[0036] Component (a) may be used alone or in combination of two or more types.

[0037] The content of component (a) is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, even more preferably 1 to 10% by mass, and particularly preferably 2 to 5% by mass, based on 100% by mass of the entire composition.

[0038] The method for producing the above-mentioned component (a) is not particularly limited, but for example, it can be produced by the method for producing component (a) described below.

[0039] For example, the above-mentioned proton donor, the aniline corresponding to the above-mentioned polyaniline, and a surfactant (e.g., a nonionic emulsifier) ​​as needed are dissolved in a water-immiscible organic solvent (e.g., a hydrocarbon solvent (preferably toluene or xylene)), an acidic aqueous solution (e.g., an aqueous phosphoric acid solution) is added thereto, the reaction solution having two liquid phases, the water-immiscible organic solvent and water, is stirred, a polymerization initiator (e.g., ammonium persulfate) is added, and polymerization is carried out. After polymerization, a water-immiscible organic solvent phase can be separated by standing, thereby obtaining a polyaniline complex water-immiscible organic solvent solution. This solution can be transferred to an evaporator, and the volatile components can be evaporated to obtain a polyaniline complex (protonated polyaniline).

[0040] (Component (b): Phenolic compound) A composition according to one aspect of the present invention can enhance the conductivity of the resulting conductive film by using a phenolic compound. Phenolic compounds are not particularly limited and are compounds represented by ArOH (where Ar is an aryl group or a substituted aryl group). Specifically, examples include phenols, o-,m- or p-cresol, o-,m- or p-ethylphenol, o-,m- or p-propylphenol, o-,m- or p-butylphenol, o-,m- or p-chlorophenol, o-,m- or p-tert-amylphenol, substituted phenols such as salicylic acid, hydroxybenzoic acid, and hydroxynaphthalene; polyhydric phenolic compounds such as catechol and resorcinol; and polymer compounds such as phenolic resins, polyphenols, and poly(hydroxystyrene).

[0041] In addition, phenolic compounds represented by the following formula (3) can be used. [ka] (In equation (3), n1 is an integer between 1 and 5 (preferably between 1 and 3). R 21 These are, respectively, an alkyl group having 1 to 10 carbon atoms (preferably 2 to 8, more preferably 3 to 7), an alkenyl group having 2 to 20 carbon atoms, an alkylthio group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkylaryl group having 7 to 20 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms.

[0042] The above R 21 The following explains this. Examples of alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, and tert-amyl. Examples of alkenyl groups include substituents that have an unsaturated bond within the molecule of the alkyl group mentioned above. Examples of cycloalkyl groups include cyclopentane and cyclohexane. Examples of alkylthio groups include methylthio and ethylthio. Examples of aryl groups include phenyl and naphthyl. Examples of alkylaryl groups and arylalkyl groups include substituents obtained by combining the alkyl group and aryl group described above. Of these groups, R 21 A methyl or ethyl group is preferred.

[0043] Furthermore, phenolic compounds represented by the following formula (3') can be used. [ka] (In formula (3'), R 22 These are alkyl groups having 1 to 20 carbon atoms, alkenyl groups having 2 to 20 carbon atoms, cycloalkyl groups having 3 to 10 carbon atoms, alkylthio groups having 1 to 20 carbon atoms, aryl groups having 6 to 20 carbon atoms, alkylaryl groups having 7 to 20 carbon atoms, or arylalkyl groups having 7 to 20 carbon atoms. R in equation (3') 22 A concrete example is R in equation (3) above. 21 It is similar to that.

[0044] Component (b) may be used alone or in combination of two or more types.

[0045] The content of component (b) is preferably 1 to 50% by mass, more preferably 5 to 45% by mass, even more preferably 10 to 40% by mass, and particularly preferably 20 to 40% by mass, based on 100% by mass of the entire composition.

[0046] The mass ratio of the content of component (a) to the content of component (b) ("content of component (a)" : "content of component (b)") may be 1:1 to 1:20, preferably 1:3 to 1:15, and more preferably 1:5 to 1:10, from the viewpoint of conductivity.

[0047] (Ingredient (c): Thickener) Component (c) is preferably a polyether compound or a cellulose compound.

[0048] Examples of polyether compounds include polyethylene oxide (EO)-polypropylene oxide (PO) copolymers (for example, EP1550H (manufactured by Meisei Chemical Industry Co., Ltd.)).

[0049] Examples of cellulosic compounds include cellulose ethers (e.g., ethylcellulose, methylcellulose), hydroxyethylcellulose, or hydroxypropylmethylcellulose. Among these, cellulose ethers are preferably used due to their high thickening effect and availability. Among cellulose ethers, ethylcellulose is preferably used.

[0050] Other examples of cellulosic compounds include EC-N300 (manufactured by Ashland), N200 (manufactured by Ashland), and Klucel G (manufactured by Ashland).

[0051] Component (c) may be used alone or in combination of two or more types.

[0052] The content of component (c) is, for example, 0.1% by mass or more, 0.2% by mass or more, 0.3% by mass or more, 0.5% by mass or more, 1.5% by mass or more, 2% by mass or more, 0.2 to 10% by mass, 0.3 to 10% by mass, 0.5 to 10% by mass, 1.5 to 5% by mass, or 2 to 3% by mass, based on 100% by mass of the entire composition.

[0053] The mass ratio of the content of component (a) to the content of component (c) ("content of component (a)" : "content of component (c)") is, from the viewpoint of conductivity, for example, 1:0.01 to 1:3, 1:0.035 to 1:2, 1:0.1 to 1:1.5, 1:0.1 to 1:1, 1:0.1 to 1:0.9, 1:0.1 to 1:0.7, 1:0.2 to 1:0.7, or 1:0.3 to 1:0.7.

[0054] (Component (d): Solvent) A composition according to one aspect of the present invention contains a solvent. The solvent is not particularly limited as long as it dissolves component (a), but an organic solvent is preferred. The organic solvent may be a water-soluble organic solvent or a substantially water-immiscible organic solvent (water-immiscible organic solvent).

[0055] Water-soluble organic solvents can be either protic or aprotic polar solvents. Examples include alcohols such as isopropyl alcohol, 1-propanol, 1-butanol, 2-butanol, 2-pentanol, benzyl alcohol, alkoxy alcohols (e.g., 1-methoxy-2-propanol, 3-methoxy-1-butanol, 3-methoxy-3-methylbutanol), and ethylene glycol; ketones such as acetone; ethers such as tetrahydrofuran, dioxane, and ethylene glycol mono-tert-butyl ether; and aprotic polar solvents such as N-methylpyrrolidone. Examples of water-immiscible organic solvents include hydrocarbon solvents such as hexane, benzene, toluene, xylene, ethylbenzene, tetralin, and IP Solvent 1620; halogen-containing solvents such as methylene chloride, chloroform, carbon tetrachloride, dichloroethane, and tetrachloroethane; ester solvents such as ethyl acetate, isobutyl acetate, n-butyl acetate, butyl butyrate, and ethyl lactate; ketone solvents such as methyl isobutyl ketone (MIBK), diisobutyl ketone (DIBK), methyl ethyl ketone, cyclopentanone, and cyclohexanone; and ether solvents such as cyclopentyl methyl ether, 4-methyltetrahydropyran, 1,2-diethoxyethane, and dipropylene glycol dimethyl ether. In addition, isoparaffinic solvents containing one or more isoparaffins may be used as hydrocarbon solvents.

[0056] Of these, toluene, xylene, methyl isobutyl ketone, chloroform, trichloroethane, and ethyl acetate are preferred in terms of their excellent solubility of component (a). Furthermore, the polyaniline complex in component (a) can be dissolved even if the solvent is an alcohol such as isopropyl alcohol, 1-butanol, 2-butanol, 2-pentanol, benzyl alcohol, or alkoxy alcohol. Alcohols are preferred over aromatics such as toluene from the viewpoint of reducing environmental impact.

[0057] When using an organic solvent as a solvent, it is preferable to use a mixed organic solvent obtained by mixing a water-immiscible organic solvent and a water-soluble organic solvent in a mass ratio of 99 to 1:1 to 99, as this prevents the formation of gels during storage and allows for long-term storage. As the water-immiscible organic solvent in the above mixed organic solvent, a low-polarity organic solvent can be used. Preferred low-polarity organic solvents include hydrocarbon solvents such as hexane and toluene; halogen-containing solvents such as chloroform; and isoparaffinic solvents. As the water-soluble organic solvent in the mixed organic solvent, highly polar organic solvents can be used, and preferred examples include alcohols such as methanol, ethanol, isopropyl alcohol, 2-methoxyethanol, 2-ethoxyethanol, 1-methoxy-2-propanol, and 3-methoxy-1-butanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; and ethers such as tetrahydrofuran, diethyl ether, and ethylene glycol mono-tert-butyl ether. The mixed organic solvent may contain one or more water-immiscible organic solvents, and may also contain one or more water-soluble organic solvents.

[0058] Component (d) may be used alone or in combination of two or more types.

[0059] The content of component (d) may be 50-99% by mass, 55-99% by mass, or 70-99% by mass, based on 100% by mass of the entire composition.

[0060] When component (d) contains 3-methoxy-3-methylbutanol, ethylene glycol, and IP Solvent 1620, it is preferable that component (b) is p-tert-amylphenol and component (c) is EC-N300. In addition, it is preferable that the "content of component (a)" : "content of component (b)" is 1:3 to 1:10, and particularly preferable that it is 1:5 to 1:8. Furthermore, it is preferable that the "content of component (a)" : "content of component (c)" is 1:0.02 to 1:2, and particularly preferable that it is 1:0.1 to 1:0.3.

[0061] When component (d) contains toluene and isopropyl alcohol, it is preferable that component (b) is m-cresol and component (c) is EC-N300. In addition, it is preferable that the "content of component (a)" : "content of component (b)" is 1:3 to 1:10, and particularly preferable that it is 1:7 to 1:9. Furthermore, it is preferable that the "content of component (a)" : "content of component (c)" is 1:0.02 to 1:5, and particularly preferable that it is 1:0.1 to 1:2.

[0062] (Component(e): Acidic substances and / or salts of acidic substances) A composition according to one aspect of the present invention may further contain an acid species different from the above-mentioned proton donor, and may further contain one or more (hereinafter also referred to as "component (e)") selected from the group consisting of acidic substances and salts of acidic substances. This component is usually used as a heat-resistant stabilizer and can further improve the heat resistance of the conductive film.

[0063] The acidic substance may be either an organic acid (an acid of an organic compound) or an inorganic acid (an acid of an inorganic compound), and is preferably an organic acid. The acidic substance is preferably an organic acid containing one or more sulfonic acid groups.

[0064] The organic acid having the above-mentioned sulfonic acid group is preferably a cyclic, linear, or branched alkyl sulfonic acid, a substituted or unsubstituted aromatic sulfonic acid, or a polysulfonic acid having one or more sulfonic acid groups. Examples of the alkyl sulfonic acids mentioned above include methanesulfonic acid and ethanesulfonic acid. Here, the alkyl group is preferably a linear or branched alkyl group having 1 to 18 carbon atoms. Examples of the above-mentioned aromatic sulfonic acids include those having 6 to 20 carbon atoms, such as sulfonic acids having a benzene ring, sulfonic acids having a naphthalene skeleton, and sulfonic acids having an anthracene skeleton. Furthermore, examples of the above-mentioned aromatic sulfonic acids include substituted or unsubstituted benzenesulfonic acid, substituted or unsubstituted naphthalenesulfonic acid, and substituted or unsubstituted anthracenesulfonic acid.

[0065] The substituents are selected from the group consisting of alkyl groups (e.g., those having 1 to 20 carbon atoms), alkoxy groups (e.g., those having 1 to 20 carbon atoms), hydroxyl groups, nitro groups, carboxyl groups, and acyl groups, and may be substituted with one or more atoms.

[0066] Specifically, examples of aromatic sulfonic acids include compounds represented by the following formulas (4) or (5). [ka] (In equation (4), l is 1 or greater, m is an integer between 0 and 5 (inclusive), and n is an integer between 0 and 5 (inclusive). If either m or n is 0, the other is 1 or greater.) [ka] (In formula (5), q is 1 or greater, p is an integer between 0 and 7, and R is independently an alkyl group, carboxyl group, hydroxyl group, nitro group, cyano group, or amino group having 1 to 20 carbon atoms.)

[0067] In equation (4), l is preferably between 1 and 3. In equation (4), m is preferably between 1 and 3. In equation (4), n is preferably between 0 and 3. In formula (5), q is preferably 1 to 3. In formula (5), p is preferably 0 to 3. In formula (5), R is preferably an alkyl group having 1 to 20 carbon atoms, a carboxyl group, or a hydroxyl group.

[0068] Examples of aromatic sulfonic acids include 4-sulfophthalic acid, 5-sulfosalicylic acid, 5-sulfosalicylic acid, 1-naphthalenesulfonic acid, 2-naphthalenesulfonic acid, 2-hydroxy-6-naphthalenesulfonic acid, p-phenolsulfonic acid, toluenesulfonic acid, p-xylene-2-sulfonic acid, 4,4'-biphenyldisulfonic acid, dibenzofuran-2-sulfonic acid, flavian acid, (+)-10-camphorsulfonic acid, monoisopropylnaphthalenesulfonic acid, and 1-pyrenesulfonic acid. Among these, 4-sulfophthalic acid, 5-sulfosalicylic acid, 5-sulfosalicylic acid, 2-naphthalenesulfonic acid, dibenzofuran-2-sulfonic acid, flavian acid, 2-hydroxy-6-naphthalenesulfonic acid, and 1-pyrenesulfonic acid are preferred from the viewpoint of improving heat resistance.

[0069] Examples of salts of acidic substances include the salts of the compounds listed above. Examples of counterions to salts include sodium, lithium, potassium, cesium, ammonium, calcium, and barium. Component (e) may be a hydrate.

[0070] Component (e) may be used alone or in combination of two or more types.

[0071] If component (e) is included, the content of component (e) is preferably 0.01 to 10% by mass, more preferably 0.02 to 5% by mass, and even more preferably 0.05 to 3% by mass, based on 100% by mass of the entire composition.

[0072] If component (e) is included, the mass ratio of the content of component (a) to the content of component (e) ("content of component (a)" : "content of component (e)") may be 1:0.01 to 1:1, preferably 1:0.05 to 1:0.5, and more preferably 1:0.07 to 1:0.1, from the viewpoint of heat resistance.

[0073] A composition according to one aspect of the present invention may essentially consist of one or more components selected from the group consisting of components (a), (b), (c), and (d), and optionally (e). In this case, other unavoidable impurities may be included as long as they do not impair the effects of the present invention. For example, a composition according to one aspect of the present invention may contain 70% or more by mass, 80% or more by mass, 90% or more by mass, 98% or more by mass, 99% or more by mass, 99.5% or more by mass, 99.9% or more by mass, or 100% by mass. Components (a) to (d), or It may consist of components (a) to (e).

[0074] [Conductive film] A conductive film according to one aspect of the present invention is made using the above-described composition. For example, a conductive film can be formed by applying a composition according to one aspect of the present invention onto a substrate and drying it. A conductive laminate may also be formed by applying the composition onto a substrate such as glass, resin film, sheet, or nonwoven fabric having a desired shape. The thickness of the conductive film is usually 1 mm or less, preferably 10 nm to 50 μm.

[0075] The conductivity of the conductive film according to one aspect of the present invention may be, for example, 0.5 S / cm or more, from the viewpoint of exhibiting its effectiveness as a conductive material. Examples include 1 S / cm or more, 4 S / cm or more, 5 S / cm or more, 9 S / cm or more, 10 S / cm or more, 20 S / cm or more, 100 S / cm or more, or 200 S / cm or more. Examples also include 400 S / cm or less, or 300 S / cm or less. The conductivity of the conductive film is determined by finding the resistance value using a four-terminal resistivity meter "Rolestar GP" (manufactured by Mitsubishi Chemical Corporation) and then calculating it using the following formula. Conductivity [S / cm] = Distance between electrodes (=1cm) ÷ (Resistance [Ω] × Film thickness [cm] × Film width [cm])

[0076] Known methods for applying the composition include casting, spraying, dip coating, doctor blade, barcode, spin coating, electrospinning, screen printing, and gravure printing.

[0077] Furthermore, the process may include a step of immersing the conductive film (coating) in a solution containing component (e) and drying it. In this case, component (e) is preferably the compound represented by formula (4) or a salt thereof.

[0078] The immersion solution may contain a solvent. The solvent is not particularly limited as long as component (e) is dissolved, and examples include water, alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, etc. One or more types may be used in combination.

[0079] Examples of solvents include methanol, ethanol, isopropanol, n-butanol, 1-methoxy-2-propanol, 3-methoxy-1-butanol, 3-methoxy-3-methylbutanol, 1-ethoxy-2-propanol, ethyl acetate, butyl acetate, MIBK, methyl ethyl ketone (MEK), ethylene glycol mono-tert-butyl ether, propylene glycol monomethyl ether acetate, and dipropylene glycol monomethyl ether.

[0080] The content of component (e) in the immersion solution is preferably 10 to 1200 parts by mass, more preferably 30 to 700 parts by mass, and even more preferably 70 to 400 parts by mass, per 1 part by mass of the composition obtained by removing the solvent. If the amount exceeds 1200 parts by mass, an excess of acidic substances may be present in the coating, potentially causing deterioration of the polyaniline main chain and a decrease in conductivity.

[0081] Furthermore, component (e) is preferably present in an amount of 0.1% to 10% by weight, more preferably 0.3% to 6% by weight, and even more preferably 0.7% to 3.5% by weight in the immersion solution.

[0082] Immersion methods include dipping. The immersion time is preferably 1 minute or more, and more preferably 3 minutes or more and 200 minutes or less. The immersion temperature is preferably 5°C to 50°C. Drying after immersion is preferably done using an oven, hot plate, or the like. The drying temperature is preferably 80 to 200°C, and more preferably 100 to 170°C. The drying time is preferably 1 to 180 minutes, and more preferably 3 to 60 minutes. If necessary, heating under reduced pressure may be used. The drying temperature and drying time are not particularly limited and should be appropriately selected depending on the material used.

[0083] As described above, component (e) may be added to the above composition or included in the conductive film obtained from the composition. Component (e) may be added to the composition, and further component (e) may be included in the conductive film obtained from the composition. That is, a conductive film according to one aspect of the present invention may include a component (e) added before film formation (hereinafter sometimes referred to as component (e1)) and a component (e) added after film formation (hereinafter sometimes referred to as component (e2)). Components (e1) and (e2) may be the same or different. If they are different, for example, component (e1) is a compound represented by the above formula (5), and component (e2) is a compound represented by the above formula (4).

[0084] [Capacitor] A capacitor according to one aspect of the present invention includes the conductive film described above. For example, a capacitor can be manufactured using a composition according to one aspect of the present invention. Specifically, examples of capacitors include electrolytic capacitors and electric double-layer capacitors, and examples of electrolytic capacitors include solid electrolytic capacitors. When manufacturing a solid electrolytic capacitor, for example, the process includes applying the composition of the present invention to the anode body, which includes the anode and dielectric of the solid electrolytic capacitor, and drying it to form a conductive film on the anode body.

[0085] A capacitor according to one aspect of the present invention has excellent heat resistance and humidity resistance, making it extremely useful, for example, in automotive applications or on circuit boards in communication base stations. Vehicles such as automobiles are sometimes subjected to harsh environments of high temperature and humidity. In addition, circuit boards in communication base stations can become hot due to electronic equipment such as power amplifiers, so capacitors used in these applications are required to have a certain level of heat resistance and humidity resistance, and the above-described capacitor can satisfy these requirements.

[0086] [battery] A battery according to one aspect of the present invention includes the conductive film described above. A conductive film according to one aspect of the present invention can be used as a battery material.

[0087] [Conductive laminates, conductive articles] A conductive laminate having a conductive film can be manufactured by applying a composition according to one aspect of the present invention to a substrate such as glass, resin film, sheet, or nonwoven fabric having a desired shape, and then removing the solvent. A conductive article can be manufactured by processing the conductive laminate into a desired shape using known methods such as vacuum forming or pressure forming. From the viewpoint of molding, the substrate is preferably a resin film, sheet, or nonwoven fabric.

[0088] Known methods such as casting, spraying, dip coating, doctor blade coating, bar coating, spin coating, electrospinning, screen printing, and gravure printing can be used to apply the composition to the substrate. When drying the coating film, the coating film may be heated depending on the type of solvent. For example, it may be heated at a temperature of 250°C or less, preferably 50°C to 200°C, under an airflow, and further heated under reduced pressure as needed. The heating temperature and heating time are not particularly limited and should be appropriately selected depending on the material used.

[0089] Furthermore, a self-supporting molded article without a substrate can also be made using a composition according to one aspect of the present invention. [Examples]

[0090] Manufacturing Example 1 (Manufacturing of Polyaniline Composites) 32.4 g of "Neocol SWC" (sodium di-2-ethylhexyl sulfosuccinate, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 13.3 g of aniline, and 0.9 g of "Sorbon T-20" (a nonionic emulsifier having a polyoxyethylene sorbitan fatty acid ester structure, manufactured by Toho Chemical Industry Co., Ltd.) were placed in a 1,000 mL separable flask and dissolved in 320.4 g of toluene. 450 g of 8.5% by mass aqueous phosphoric acid solution was added, and the reaction solution, which had two liquid phases of toluene and water, was stirred and the internal temperature of the reaction solution was cooled to -3°C. When the internal temperature of the reaction solution reached -3°C, a solution of 39.3 g of APS (ammonium persulfate) dissolved in 90.2 g of 8.5% by mass aqueous phosphoric acid solution was added while stirring the reaction solution. After adding the solution, stirring was continued for 24 hours while maintaining the internal temperature of the solution at -3°C. After stopping stirring, the contents were transferred to a separatory funnel and the aqueous phase and toluene phase were separated by standing. After separation, the toluene phase was washed once with 180.3 g of 8.5% by mass aqueous phosphoric acid solution and three times with 328.0 g of deionized water to obtain a polyaniline complex toluene solution. This solution was transferred to an evaporator, heated in a 60°C water bath, and the volatile components were evaporated by reduced pressure to obtain polyaniline complex 1 (protonated polyaniline). The weight-average molecular weight of polyaniline in polyaniline complex 1 was 112,000.

[0091] The weight-average molecular weight of polyaniline was measured as follows. A 0.01 M lithium bromide NMP solution was prepared by dissolving 1.65-1.85 g of lithium bromide in 2000 ml of NMP (N-methyl-2-pyrrolidone). 14 μL of triethylamine was added to 10 ml of this 0.01 M lithium bromide NMP solution and stirred until dissolved and a homogeneous solution was obtained. Furthermore, 50 μL of the polyaniline complex toluene solution obtained in Preparation Example 1 was added dropwise, stirred and mixed, and then the mixture was passed through a 0.45 μm filter to prepare a sample for gel permeation chromatography (GPC) measurement. Using samples for GPC measurement, GPC measurements were performed using a GPC column (Shodex KF-806M manufactured by Showa Denko K.K., 2 columns linked together) under the following measurement conditions. Solvent: 0.01ML iBr-containing NMP Flow rate: 0.70mL / min Column temperature: 60℃ Injection volume: 100μL UV detection wavelength: 270nm The weight-average molecular weight obtained by the above method is the polystyrene (PS) equivalent value.

[0092] Furthermore, the doping rate of the proton donor (sodium di-2-ethylhexyl sulfosuccinate) to polyaniline was 0.36.

[0093] Example 1 (Preparation of Composition) Mixed solvent A was prepared by stirring and mixing 30g of 3-methoxy-3-methylbutanol (MMB), 10g of ethylene glycol (EG), 20g of IP Solvent 1620 (IP1620, manufactured by Idemitsu Kosan Co., Ltd.), and 40g of p-tert-amylphenol (tAP) (component (b)) until homogeneous. 5g of polyaniline complex 1 and 0.1g of EC-N300 (N300, ethylcellulose, a compound with the structure shown below, manufactured by Ashland) were dissolved in 94.9g of mixed solvent A to obtain polyaniline complex solution 1. 1 g of 2-naphthalenesulfonic acid (NSA) hydrate (since the amount of hydrate is trace, we used 1 g of NSA) was dissolved in 9 g of 3-methoxy-3-methylbutanol (MMB) to obtain a homogeneous 2-naphthalenesulfonic acid solution 1. 5 g of polyaniline complex solution 1 was mixed with 0.188 g of 2-naphthalene sulfonic acid solution 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. In Table 1, component (d) is shown as the total amount of each component (d) (the same applies hereafter). [ka]

[0094] (Viscosity measurement) Viscosity measurements were performed on the obtained compositions using a tuning fork type vibrating viscometer SV-1H (manufactured by A&D Company, Limited) at a liquid temperature in the range of 23-24°C. The results are shown in Table 1.

[0095] (Manufacturing of conductive films) As shown in Figure 1, 1 ml of the above composition was applied to the upper surface of a glass substrate 1 on which an indium tin oxide (ITO) electrode 2 had been formed by patterning. The application was performed by spin coating in an atmospheric environment. The rotation time of the glass substrate 1 after dropping the composition was 15 seconds, and the rotation speed of the glass substrate 1 was 2000 to 2500 rpm. After that, the glass substrate 1 was dried to form a conductive film. It was dried at 80°C for 5 minutes.

[0096] (Evaluation of conductive films (conductivity)) As shown in Figure 2, the portion of the obtained conductive film 5 that covered the terminals of the ITO electrode was scraped off in an atmospheric environment, exposing the terminals of the ITO electrode 2 to the surface. The resistance value was measured using the exposed ITO electrode 2 with a four-terminal resistivity meter "Rolestar GP" (manufactured by Mitsubishi Chemical Corporation). Furthermore, the film thickness and width of the conductive film were measured using a scanning white light interference microscope VS1330 (manufactured by Hitachi High-Tech Corporation). From the above measured values, the conductivity of the conductive film was calculated using the following formula. Conductivity [S / cm] = Distance between electrodes (=1cm) ÷ (Resistance [Ω] × Film thickness [cm] × Film width [cm]) The results are shown in Table 1.

[0097] Example 2 5 g of polyaniline complex 1 and 0.5 g of N300 were dissolved in 94.5 g of mixed solvent A prepared in Example 1 to obtain polyaniline complex solution 2. 5 g of polyaniline complex solution 2 was mixed with 0.188 g of 2-naphthalene sulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. The obtained compositions were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0098] Example 3 Mixed solvent B was prepared by stirring and mixing 37.5g of MMB, 12.5g of EG, 25g of tAP, and 25g of IP1620 until homogeneous. Polyaniline complex solution 3 was obtained by dissolving 5g of polyaniline complex 1 and 0.5g of N300 in 94.5g of this mixed solvent B. 5 g of polyaniline complex solution 3 was mixed with 0.188 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. The obtained compositions were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0099] Comparative Example 1 Mixed solvent C was prepared by stirring and mixing 50g of MMB, 17g of EG, and 33g of IP1620. Mixed solvent C did not dissolve uniformly. 5g of polyaniline complex 1 and 0.5g of N300 were added to 94.5g of mixed solvent C to obtain polyaniline complex solution 4. In this polyaniline complex solution 4, polyaniline complex 1 did not dissolve, resulting in a heterogeneous solution. 5 g of polyaniline complex solution 4 was mixed with 0.188 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. Because polyaniline composite 1 did not dissolve in this composition, resulting in a heterogeneous composition, accurate viscosity measurement was not possible. This is indicated by "-" in Table 1 (the same applies hereafter). Furthermore, although a coating film was prepared by the spin-coating method in the same manner as in Example 1, a uniform coating film could not be produced, the resistance value was above the measurement limit, and a conductive coating film could not be produced. This is indicated by "-" in Table 1 (the same applies hereafter).

[0100] Comparative Example 2 5 g of polyaniline complex 1 was dissolved in 95 g of mixed solvent A prepared in Example 1 to obtain polyaniline complex solution 5. 5 g of polyaniline complex solution 5 was mixed with 0.188 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. The obtained compositions were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0101] Comparative Example 3 5 g of polyaniline complex 1 was added to 95 g of mixed solvent C prepared in Comparative Example 1 to obtain polyaniline complex solution 6. Polyaniline complex 1 did not dissolve in this mixed solvent C, resulting in a heterogeneous solution. 5 g of polyaniline complex solution 6 was mixed with 0.188 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. Because the polyaniline complex 1 did not dissolve in this composition, resulting in a heterogeneous composition, accurate viscosity measurements could not be performed. Furthermore, although a coating film was prepared by the spin coating method in the same manner as in Example 1, a uniform coating film could not be produced, the resistance value was above the measurement limit, and a conductive coating film could not be produced.

[0102] Comparative Example 4 5 g of polyaniline complex 1 was dissolved in 95 g of mixed solvent B prepared in Example 3 to obtain polyaniline complex solution 7. 5 g of polyaniline complex solution 7 was mixed with 0.188 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. The obtained compositions were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0103] Examples 11-13, Examples 21-22, Examples 31-32, Comparative Example 11, Comparative Example 21, and Comparative Example 31 Examples 11, 21, and 31 were manufactured and evaluated in the same manner as in Example 1, except that component (c) shown in Tables 2-4 was used. The results are shown in Tables 2-4. Examples 12, 22, and 32 were manufactured and evaluated in the same manner as in Example 2, except that component (c) shown in Tables 2-4 was used. The results are shown in Tables 2-4. Comparative Examples 11, 21, and 31 were manufactured and evaluated in the same manner as Comparative Example 1, except that component (c) shown in Tables 2-4 was used. The results are shown in Tables 2-4.

[0104] Example 13 5 g of polyaniline complex 1 and 1.0 g of N200 were dissolved in 94 g of mixed solvent A prepared in Example 1 to obtain polyaniline complex solution 8. 5 g of polyaniline complex solution 8 was mixed with 0.188 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. The obtained compositions were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0105] (Evaluation of viscosity ratio 1) Tables 1-4 show the viscosity values ​​obtained by dividing the viscosity value of Comparative Example 2 in Examples 1-3, 11-13, 21-22, 31-32, Comparative Examples 1-4, 11, 21, and 31. "-" indicates that evaluation was not possible.

[0106] The component (c) other than that used in Example 1 is shown below. N200: Ethylcellulose, a compound with the structure shown below, manufactured by Ashland. [ka] G: Klucel G, hydroxypropylcellulose, a compound with the structure shown below, manufactured by Ashland. [ka]

[0107] EP1550H: Ethylene oxide / propylene oxide copolymer, manufactured by Meisei Chemical Industry Co., Ltd.

[0108] [Table 1]

[0109] [Table 2]

[0110] [Table 3]

[0111] [Table 4]

[0112] Example 41 7 g of polyaniline complex 1 and 1 g of N300 were dissolved in 92 g of mixed solvent A prepared in Example 1 to obtain polyaniline complex solution 9. 5 g of polyaniline complex solution 9 was mixed with 0.263 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. The obtained compositions were evaluated in the same manner as in Example 1. The results are shown in Table 5.

[0113] Example 42 7 g of polyaniline complex 1 and 2 g of N300 were dissolved in 91 g of mixed solvent A prepared in Example 1 to obtain polyaniline complex solution 10. 5 g of polyaniline complex solution 10 was mixed with 0.263 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. The obtained compositions were evaluated in the same manner as in Example 1. The results are shown in Table 5.

[0114] Comparative Example 41 7 g of polyaniline complex 1 was dissolved in 93 g of mixed solvent A prepared in Example 1 to obtain polyaniline complex solution 11. 5 g of polyaniline complex solution 11 was mixed with 0.263 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. The obtained compositions were evaluated in the same manner as in Example 1. The results are shown in Table 5.

[0115] (Evaluation of viscosity ratio 2) Table 5 shows the values ​​obtained by dividing the viscosity values ​​of Examples 41-42 and Comparative Example 41 by the viscosity value of Comparative Example 41.

[0116] [Table 5]

[0117] Example 51 10 g of polyaniline complex 1 and 1 g of N300 were dissolved in 89 g of mixed solvent A prepared in Example 1 to obtain polyaniline complex solution 12. 5 g of polyaniline complex solution 12 was mixed with 0.376 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. The obtained compositions were evaluated in the same manner as in Example 1. The results are shown in Table 6.

[0118] Comparative Example 51 10 g of polyaniline complex 1 was dissolved in 90 g of mixed solvent A prepared in Example 1 to obtain polyaniline complex solution 13. 5 g of polyaniline complex solution 13 was mixed with 0.376 g of 2-naphthalenesulfonic acid solution 1 prepared in Example 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain the composition. The obtained compositions were evaluated in the same manner as in Example 1. The results are shown in Table 6.

[0119] (Evaluation of viscosity ratio 3) Table 6 shows the values ​​obtained by dividing the viscosity values ​​of Example 51 and Comparative Example 51 by the viscosity value of Comparative Example 51.

[0120] [Table 6]

[0121] Example 61 (Preparation of Composition) Mixed solvent D was prepared by stirring 95 g of toluene (Tol) and 5 g of isopropyl alcohol (IPA) until homogeneous. Polyaniline complex 1 and 0.03 g of EC-N300 (N300, ethylcellulose, a compound with the structure shown below, manufactured by Ashland) were dissolved in 7.25 g of mixed solvent D to obtain polyaniline complex solution 14. 2.42 g of m-cresol was added to the above polyaniline complex solution 14, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain a total of 10 g of composition.

[0122] The viscosity of the obtained composition was measured in the same manner as in Example 1. Furthermore, the conductivity of the obtained conductive film was determined in the same manner as in Example 1. The results are shown in Table 7.

[0123] Examples 62-69 and Comparative Examples 61-65 The preparation and evaluation were carried out in the same manner as in Example 61, except for the formulation amounts shown in Tables 7 and 8. The results are shown in Tables 7 and 8.

[0124] (Evaluation of viscosity ratio 4) Tables 7 and 8 show the viscosity values ​​obtained by dividing the viscosity values ​​of each example (61-69) and comparative examples (61-65) by the viscosity value of comparative example (65).

[0125] Figure 3 shows the synergistic effect of component (b) and component (c) using Examples 61-65 and Comparative Examples 61-64. Examples 61-65 contain 24.2% by mass of component (b). On the other hand, Comparative Examples 61-64 do not contain component (b). The vertical axis represents viscosity, and the horizontal axis represents the amount of component (c) added. Even at low concentrations of component (c), an increase in viscosity due to the synergistic effect of components (b) and (c) was observed (indicated by solid arrows at both ends in Figure 3). However, as the amount of component (c) increased, a significant increase in viscosity due to the synergistic effect of components (b) and (c) was observed (indicated by dashed arrows at both ends in Figure 3).

[0126] [Table 7]

[0127] [Table 8] [Industrial applicability]

[0128] The composition and conductive film of the present invention can be used in capacitors, batteries, and the like. [Explanation of symbols]

[0129] 1. Glass substrate 2 ITO electrode 5. Conductive film

Claims

1. (a) conductive polymer, (b) a phenolic compound, (c) a thickening agent, and (d) a solvent.

2. 2. The composition according to claim 1, wherein the component (a) is a polyaniline complex in which a substituted or unsubstituted polyaniline is doped with a proton donor.

3. The composition according to claim 2 , wherein the proton donor is a proton donor represented by the following formula (I): M(XARn)m(I) In formula (I), M is a hydrogen atom, an organic free radical, or an inorganic free radical. X is an acidic group, and A is a hydrocarbon group which may contain a substituent. Each R is independently -R 1 , -OR 1 , -COR 1 , -COOR 1 , -CO(COR 1 ), or -CO(COOR 1 ) is a substituent represented by the formula: R 1 represents a hydrocarbon group having 4 or more carbon atoms which may contain a substituent, a silyl group, an alkylsilyl group, -(R 2 O) x -R 3 or a group represented by -(OSiR 3 2 ) x -OR 3 (R 2 is an alkylene group, R 3 are hydrocarbon groups which may be the same or different, and x is an integer of 1 or more. n is an integer of 2 or more. m is the valence of M.

4. The composition according to any one of claims 1 to 3, wherein the content of the component (c) is 0.1 mass% or more with respect to 100 mass% of the entire composition.

5. The composition according to any one of claims 1 to 3, wherein a mass ratio of the content of the component (a) to the content of the component (c) is 1:0.01 to 1:

2.

6. The composition according to any one of claims 1 to 3, wherein the component (c) is a polyether compound or a cellulose compound.

7. The composition according to any one of claims 1 to 3, having a viscosity of 2 to 1000 mPa·s.

8. A conductive film obtained by using the composition according to any one of claims 1 to 3.

9. A capacitor comprising the conductive film of claim 8.

10. A battery comprising the conductive film of claim 8.